PENGARUH RASIO KEUANGAN DAN RASIO PASAR TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010 â 2013 - Khafindatul Mukharomah, 11.05.52.0072; ., Sunarto (Students Journal of Accounting and Banking, 2015)
This study examines the effect of Earning Per Share, Debt to Equity Ratio, Return On Asset, Price to Book Value of the stock return. This research was conducted at the Indonesian Stock Exchange by using go public manufacturing compaines period 2010-2013. This sampling method used purposive sampling with the observationperiod from 2010-2013. The sample of this study where 72 manufacturing company that meet the criteria. Relationship and (or) influence between variable is describe by using multiple regression analysis. The result show that the Earning Per Sahare,Debt to Equity Ratio, and Price to Book Value had no significant effect on stock Return. Whearess the Return On Assets significant to the Stock return.Keywords: Earning Per Share, Debt to Equity Ratio, Return On Asset, Price to Book Value and Stock Return